2002
DOI: 10.1038/sj.bjc.6600190
|View full text |Cite
|
Sign up to set email alerts
|

Prostate-Specific Ets (PSE) factor: a novel marker for detection of metastatic breast cancer in axillary lymph nodes

Abstract: Prostate Specific Ets factor is a recently identified transcriptional activator that is overexpressed in prostate cancer. To determine whether this gene is overexpressed in breast cancer, we performed a virtual Northern blot using data available online at the Cancer Genome Anatomy Project website. Ninety-five SAGE libraries were probed with a unique sequence tag to the Prostate Specific Ets gene. The results indicate that Prostate Specific Ets is expressed in 14 out of 15 breast cancer libraries (93%), nine ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 19 publications
0
27
0
Order By: Relevance
“…Intronspanning primers were designed and tested in breast cancer cell lines MDA-MB-231 or SK-BR-3: TFF1 forward 5V -AATGGCCACCATGGA-GAACA-3V , reverse 5V -ACCACAATTCTGTCTTTCACGG-3V ; TFF3 forward 5V -TTTGACTCCAGGATCCCTGGAG-3V , reverse 5V -AGGTGCCTCA-GAAGGTGCATTC-3V ; PRO1708 forward 5V -AAGAATGCCCTGTGCA-GAAGAC-3V , reverse 5V -TTCTGTGCAGCATTTGGTGACT-3V ; Lipophilin B forward 5V -ACGGATCAGATGTCCCTTCAG-3V , reverse 5V -TTGAAAGA-CAGTGGAAACCAGG-3V ; FBJ forward 5V -CGTTGTGAAGACCATGA-CAGGA-3V , reverse 5V -TCCTTTCCCTTCGGATTCTCC-3V . Primers to the mam gene has been previously described (11,12). cDNA was made from 5 Ag of total RNA using 200 units of Moloney murine leukemia virus reverse transcriptase (Promega, Madison, WI) and 0.5 Ag Oligo (dT) [12][13][14][15][16] in a reaction volume of 20 AL (10 minutes at 70jC, 50 minutes at 42jC, and 15 minutes at 70jC).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Intronspanning primers were designed and tested in breast cancer cell lines MDA-MB-231 or SK-BR-3: TFF1 forward 5V -AATGGCCACCATGGA-GAACA-3V , reverse 5V -ACCACAATTCTGTCTTTCACGG-3V ; TFF3 forward 5V -TTTGACTCCAGGATCCCTGGAG-3V , reverse 5V -AGGTGCCTCA-GAAGGTGCATTC-3V ; PRO1708 forward 5V -AAGAATGCCCTGTGCA-GAAGAC-3V , reverse 5V -TTCTGTGCAGCATTTGGTGACT-3V ; Lipophilin B forward 5V -ACGGATCAGATGTCCCTTCAG-3V , reverse 5V -TTGAAAGA-CAGTGGAAACCAGG-3V ; FBJ forward 5V -CGTTGTGAAGACCATGA-CAGGA-3V , reverse 5V -TCCTTTCCCTTCGGATTCTCC-3V . Primers to the mam gene has been previously described (11,12). cDNA was made from 5 Ag of total RNA using 200 units of Moloney murine leukemia virus reverse transcriptase (Promega, Madison, WI) and 0.5 Ag Oligo (dT) [12][13][14][15][16] in a reaction volume of 20 AL (10 minutes at 70jC, 50 minutes at 42jC, and 15 minutes at 70jC).…”
Section: Methodsmentioning
confidence: 99%
“…Primers to the mam gene has been previously described (11,12). cDNA was made from 5 Ag of total RNA using 200 units of Moloney murine leukemia virus reverse transcriptase (Promega, Madison, WI) and 0.5 Ag Oligo (dT) [12][13][14][15][16] in a reaction volume of 20 AL (10 minutes at 70jC, 50 minutes at 42jC, and 15 minutes at 70jC). Real-time RT-PCR analysis was done on a PE Biosystems Gene Amp 5700 Sequence Detection System (Foster City, CA).…”
Section: Methodsmentioning
confidence: 99%
“…These transcription factors regulate a number of biological processes, including cell proliferation, differentiation and invasion and are thought to play an important role in oncogenesis. Unlike the majority of Ets factors, SPDEF is expressed exclusively in tissues with a high epithelial content, such as the prostate and the breast (Oettgen et al 2000, Ghadersohi & Sood 2001, Mitas et al 2002. Furthermore, several studies showed SPDEF to be one of the most highly overexpressed mRNAs in human and mouse mammary tumours (Ghadersohi & Sood 2001, Mitas et al 2002, Galang et al 2004.…”
Section: Spdefmentioning
confidence: 99%
“…29,30 Porphobilinogen deaminase 31 and ␤-actin were used as housekeeping genes. Primers and hydrolysis probes for each assay are listed in Table 2.…”
Section: Reverse Transcription and Quantitative Polymerase Chain Reacmentioning
confidence: 99%